A study of modulus rupture and water absorption of cement mortars with replacement of palm oil fuel ash (PDFA) - Kok, Jun Jie (2014)
This thesis deals with the use of palm oil fuel ash (POFA) as the cement substitution to the Ordinary Portland Cement for the use of cement mortar. It is an attractive approach whereby POFA has been abundance in Malaysia and little research has been done on it. Furthermore, this research also involved the percentage of water absorption of each mix at 7th day and 28th day of cement maturation. The main objective of the study is to find out the best modulus of rupture (apparent tensile strength) from the various amount of POFA added into the mix and the best rate of water absorption from the samples. The tensile tests were carried out for different mortar beam samples with the used of strain gauge. Both 7th day and 28" day cement mortar maturation days were tested to compared its early strength and strength upon maturation. Graphs were plotted to make compares between the samples. The samples are then to be kept until all the testing is done on 7th and 28th days. The samples were then to be dry in oven for 24 hours before conducting the water absorption test. Dry samples were then immersed in water for another 24 hours to get its best water absorption rate. Data were tabulated and analysed. The optimum percentage of POFA that gives the optimum modulus of rupture for the cement mortar beam is 2% whereas for the water absorption, it can be concluded that as amount of POFA increased, the water will be less absorbed by the cement mortar due to POFA's fine properties that fill in the void in the cement mortars. The variation content of POFA was 0%, 1%, 2%, 3% and 4% by total cement weight.